Influence of Doping and Tunneling Interface Stoichiometry on n+In0.5Ga0.5As/p+GaAs0.5Sb0.5 Esaki Diode Behavior. (25th April 2016) - El Kazzi, Salim; Alireza, A; Bordallo, Caio Cesar Mendes; Smets, Quentin; Desplanque, Ludovic; Wallart, Xavier; Richard, Olivier; Douhard, Bastien; Verhulst, Anne; Collaert, Nadine; Merckling, Clement; Heyns, Marc; et al.
Abstract : In this work, we study the influence of molecular beam epitaxy (MBE) growth parameters on the behavior of a staggered band gap n+In0.5 Ga0.5 As/p+GaAs0.5 Sb0.5 Esaki diodes. We first first show that a careful doping is required to avoid any crystal defects. Then the influence of the doping concentration on the Band to Band Tunneling (BTBT) is discussed. At the end, we show that a careful monitoring of the MBE growth allows thin and abrupt n+In0.5 Ga0.5 As/p+GaAs0.5 Sb0.5 tunneling interfaces where BTBT behavior in this case is independent of the III-V interface stoichiometry